Household Consumption in Japan : Role of Income and Asset Developments - Vihriala, Erkki (IMF Working Papers; Working Paper, 2017)
We study Japanese household consumption at a disaggregated level focusing on the role of income and asset dynamics. Stagnation of real per capita consumption is widespread acrosslabor market groups, age groups and regions. Consumption-to-income ratios have been mildly increasing due to the rising share of pensioners with significant assets. Evidence therefore suggests that assets have become more important in financing consumption. However, the short-term consumption dynamics remain quite sensitive to income growth but not to asset market movements.